2022
DOI: 10.1108/k-08-2022-1076
|View full text |Cite
|
Sign up to set email alerts
|

Substitute vs permanent teacher job satisfaction: applying MUSA to delineate differences and highlight evidence-based guidelines for decision makers

Abstract: PurposeThe purpose of this paper is threefold. First, to explore the importance of specific work environment facets for the overall job satisfaction (JS) of primary full-time permanent teachers (PTs) and substitute/temporary teachers (STs). Second, to highlight the similarity or difference in JS patterns among PTs and STs. Third, to provide guidelines for effective evidence-based human resource management (HRM) interventions targeting to boost PTs and STs JS levels by considering: (1) the perceived importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…These findings have also been identified in the international literature. Studies have suggested that teachers who work as substitutes or are hourly paid exhibit higher levels of stress and lower levels of job satisfaction compared to those who have a permanent job (Glaveli et al, 2022;Quinn et al, 2022).…”
Section: Journal Of School and Educational Psychologymentioning
confidence: 99%
“…These findings have also been identified in the international literature. Studies have suggested that teachers who work as substitutes or are hourly paid exhibit higher levels of stress and lower levels of job satisfaction compared to those who have a permanent job (Glaveli et al, 2022;Quinn et al, 2022).…”
Section: Journal Of School and Educational Psychologymentioning
confidence: 99%